Erdmann, Axel, Alberto Govi y Fabrizio Govi (2014): Ars Epistolica. Communication in Sixteenth Century Western Europe: Epistolaries, Letter-Writing Manuals and Model Letter Books 1501-1600 - Espejo Cala, Carmen (RIHC. Revista Internacional de Historia de la Comunicación, 2014)
Ars Epistolica. Communication in Sixteenth Century Western Europe: Epistolaries, Letter-Writing Manuals and Model Letter Books 1501-1600 Erdmann, Axel, Alberto Govi y Fabrizio Govi Lucerna, Gilhofer & Ranschburg GmbH/Libreria Alberto Govi di Fabrizio Govi S.a.s, 2014. 771 págs.